Magnet Modification to Reduce Pulsating Torque for Axial Flux Permanent Magnet Synchronous Machines - Wu, Shuanglong; Zuo, Shuguang; Wu, Xudong; Lin, Fu; Shen, Jian (Applied Computational Electromagnetics Society Journal (ACES), 2021)
To reduce pulsating torque without sacrificing the average torque significantly in axial flux permanent magnet synchronous machines (AFPMSM), this paper presents two optimization techniques which are based on magnet modification: i) combine magnet circumferential displacement with various pole-arc ratios (method one); ii) magnet axial shape design (method two). Firstly, analytical models of air gap magnetic field were derived for the above two methods. Then, according to Maxwell stress tensor method, the analytical expressions of cogging torque and electromagnetic torque were obtained. Average torque, cogging torque and electromagnetic torque ripple were considered simultaneously in the optimization using multi-objective genetic algorithm (MOGA) with the help of the analytical torque models. Finally, 3D finite element models were established to verify the two torque optimization methods. The proposed methods were also compared with skew technique, which is widely used nowadays. Result showed that the proposed optimization techniques can greatly reduce the overall pulsating torque without decreasing the average torque and did not increase the use of permanent magnet.